Domesticating the Euro - Lorenzo Bini Smaghi; Michala Marcussen (Intereconomics, 2019)
We find the litmus test is whether governments gain access to a safe source of funding in a 'domestic' currency. Of the list of solutions considered, both Purple bonds and E-bonds can meet this criterion.
Keywords: 330